Witnessing versus Fiction: Julia Frey’s diary of September 11, 2001 and Last Fall (2005) by Ronald Sukenick, her husband - Julia FREY (E-REA)
This presentation compares brief excerpts of three texts, by two authors, living together at Ground Zero on 9/11/2001. Comparison of Sukenick’s page of handwritten notes found among his papers after his death to the description of 9/11/2001 in his posthumously published novel, Last Fall (2005), shows the evolution from brief phrases to elaborated description, but confirms that the events themselves are not fictionalized in the novel. Comparison of Sukenick’s fictionalized version to Frey’s eye-witness account, written at dawn on 12/09/2001, looking out their apartment windows at the burning ruins, shows that the two accounts remain essentially identical, although Frey provides much greater detail and does not appear to be preoccupied by stylistic concerns. Frey has recently completed her own (forthcoming) novel, which includes her non-fiction account of events during and after the attacks on the World Trade Center, quoted with small changes, directly from her diary. The text is available online http://juliafrey.blogspot.com/ > Balcony View - a 9/11 Diary In looking at the ur texts for each writer’s novel, it is clear that both Sukenick and Frey chose NOT to fictionalize the events of 9/11 itself, which were dramatic enough to need no embroidery. In their novels, Frey and Sukenick use their actual experiences of 9/11 in the same way: they displace them into a fictional structure, showing them as happening to fictional characters, and as having an impact on the novel’s plot structure. In each novel the physical and emotional impact of 9/11 serves as a turning point, a cataclysmic and totally unexpected event which interrupts the flow of everyday life and changes the relationships among the novels’ characters. This fictional use of the attacks plays the role that the attacks actually played in the lives of the writers.